ANTIBACTERIAL ACTIVITY AND GAS CHROMATOGRAPHY–MASS SPECTROMETRY STUDIES OF ALGERIAN ATRIPLEX HALIMUS L. - L, ZIANE; M, DJELLOULI; A, MILOUDI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to find out the antibacterial efficacy and identify the main constituents of the essential oil of Atriplex halimus from southwest of Algeria. Methods: The essential oil from the aerial parts of the endemic plant A. halimus (saltbush in English, qataf in Arabic) collected from the region of Sahara southwest of Algeria was isolated by hydrodistillation and analyzed by gas chromatography–mass spectrometry. Antibacterial potency of essential oil from this plant has been tested against Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), and Bacillus cereus (ATCC11778) by disk diffusion assay. Results: The essential oil revealed the presence of 14 components, the dominant compounds arecadina-1(10), 4-diene (10.69%), germacrene D (9.79%), octane (9.37%), pelargonaldehyde (9.06%), 3-Furancarboxaldehyde (6.87%), β-pinene (2.6%), camphene (2.59%), and myrcene (2.10%). The essential oil exhibits very effective antimicrobial activity using disk diffusion assay method with minimum inhibitory concentration ranging from 0.82 μl/ml to 2.4525 μl/ml. Conclusions: This result showed that this native plant may be a good candidate for further biological and pharmacological investigations.